EFECTO DEL PRE-TRATAMIENTO ÁCIDO Y POR CONGELACIÓN DE FIBRA DE CORONTA DE MAÍZ (Zea mays L.) EN LA HIDRÓLISIS CON CELULASA (E.C: 3.2.1.4) - Echevarria Perez, Carlos Eduardo (2017)
Corncob has a high percentage of cellulose (40.95 ± 0.38%) and hemicellulose (38.94 ± 1.72%) and low lignin content (16.54 ± 0.38%) which has a great potential of bioconversion to bioethanol. The objective of this research was to evaluate the effect of pre-treatment, freezing and the combination of these in corn corona fiber in cellulase hydrolysis, changes in macrostructure and lignocellulosic compounds after pre-treatments. Corncob fiber (FCH) was pre-treated by freezing -20 ° C for 12 h (FCHC); With 0.25M H2SO4 at 121 ° C for 20 minutes (FCHA) and also by the combination of both pre-treatments (FCHAC). To the pre-treated samples, enzymatic hydrolysis with 150 Ucellulase / gsubstrate in 10 ml of acetate was performed at 100 rpm for 72 h, at 37 ° C and pH 5.5. The results showed that after the pre-treatments, the FCHAC contained higher cellulose (64.12 ± 1.03%), lower hemicellulose (10.16 ± 1.42%) and increased lignin (19.76 ± 0.42%). The glucose content of the final hydrolyzate of the samples with and without pretreatment: FCH, FCHC, FCHA and FCHAC were 33.17 ± 2.03 g / L, 29.50 ± 1.23 g / L, 21.92 ± 1.23 g / L and 40.90 ± 2.11 g / L respectively. The analysis of the optical microscopy of the FCHAC a comparison of the FCH and the other samples was observed more partition, and less added a structure in the form of red crystal. The higher concentration of glucose was obtained by FCHAC, these values show that the combined pre-treatment not only increases the efficiency of the enzyme, but also that it is an environmentally friendly and economically viable method for the production of glucose and lignin, which Was approved for the conversion of high value products.